Climate Risk Management for Agricultural Extension (CRMAE) Training-of-Trainers for MASAE Bureau for Professional Agricultural Training - Hansen, James; Diop, Mbaye; Trzaska, Sylwia; Serigne, Cisse; Worou, Omonlola Nadine; Wane, Abdrahmane (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
The Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA) project aims to enhance access and use of climate information services (CIS) and validated climate-smart agriculture technologies in Africa, to help these countries strengthen the resilience of their agricultural sectors to the threat posed by climate change. Strengthening the capacity of next users, particularly agricultural extension and advisory service (EAS) providers who work to support farmers in Senegal and five other target countries, is crucial for achieving this goal.